2018
DOI: 10.4187/respcare.05771
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Physical Activity With Bronchiectasis

Abstract: BACKGROUND: Bronchiectasis leads to reduced functional capacity, which might have implications for physical activity. The impact of dyspnea and long-term oxygen therapy on physical activity has never been investigated in subjects with bronchiectasis. Based on these findings, specific strategies could be applied to allow individuals to be more active in their daily life. In this study we aimed to evaluate physical activity, the impact of dyspnea and long-term oxygen therapy on physical activity, and the determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
2
16
0
3
Order By: Relevance
“…7,23 Our group has previously demonstrated that people with bronchiectasis present an important reduction in daily physical activity. 3 The HBPR proposed in this study demonstrate an increase in daily steps above the minimum important difference values for people with COPD (600 steps). 30 The improvement in physical activity after HBPR in people with bronchiectasis has been previously demonstrated using a questionnaire, 10 something that was confirmed in our study through direct measurement using accelerometers.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…7,23 Our group has previously demonstrated that people with bronchiectasis present an important reduction in daily physical activity. 3 The HBPR proposed in this study demonstrate an increase in daily steps above the minimum important difference values for people with COPD (600 steps). 30 The improvement in physical activity after HBPR in people with bronchiectasis has been previously demonstrated using a questionnaire, 10 something that was confirmed in our study through direct measurement using accelerometers.…”
Section: Discussionmentioning
confidence: 64%
“…Our group has demonstrated previously that people with bronchiectasis present an important reduction in daily physical activity [ 3 ]. The HBPR proposed in this study demonstrate an increase in daily steps above the minimum important difference values for people with COPD (600 steps) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects with bronchiectasis often suffer from respiratory symptoms (1), decreased physical activity (9,10), impaired quality of life (11)(12)(13), and comorbidities (14). In addition, bronchiectasis is associated with markedly increased healthcare costs and mortality (5,14).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above mechanistic factors, recent research that has shown PA is low in patients with noncystic fibrosis bronchiectasis relative to non-diseased controls; and positively associated with measures of lung function and exercise performance [15]. Given these factors, we believe that it is more likely that reduced PA is responsible for low BMD in this population, and not the HIF-1α pathway, although we admittedly do not have evidence to completely refute the HIF-1α pathway.…”
Section: Commentarymentioning
confidence: 75%